1988
DOI: 10.1128/jvi.62.3.866-874.1988
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the vaccinia virus growth factor gene reduces virus virulence

Abstract: the construction of a vaccinia virus mutant which lacks a functional VGF gene. The VGFmutant replicated less efficiently than did the wild-type (WT) virus in resting Swiss 3T3 cells and exhibited an attenuated phenotype following intracranial (i.c.) and intradermal inoculations into mice and rabbits, respectively. MATERIALS AND METHODS Cells and viruses. The vaccinia virus WR strain, originally obtained from the American Type Culture Collection Rockville, Md., was propagated in HeLa cells and purified as repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
78
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(83 citation statements)
references
References 45 publications
5
78
0
Order By: Relevance
“…The major phenotypic changes resulting from O1L deletion in CVA were very similar to the reported phenotypes of a vaccinia virus deletion mutant lacking the EGF-like viral growth factor gene in the VACV-WR strain background (4,43). These VACV-⌬VGF mutants also showed reduced plaque size but almost wildtype-like viral yields and lower lethality after intracranial infection of mice, as well as smaller skin lesions in rabbits.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The major phenotypic changes resulting from O1L deletion in CVA were very similar to the reported phenotypes of a vaccinia virus deletion mutant lacking the EGF-like viral growth factor gene in the VACV-WR strain background (4,43). These VACV-⌬VGF mutants also showed reduced plaque size but almost wildtype-like viral yields and lower lethality after intracranial infection of mice, as well as smaller skin lesions in rabbits.…”
Section: Discussionsupporting
confidence: 73%
“…Poxviruses generally appear to benefit from activation of this pathway in their natural hosts, since poxviruses from most genera have been shown to express a secreted growth factor similar to mammalian EGF, resulting in upregulation of ERK1/2 activation (40,57). The vaccinia virus growth factor (VGF) (4,5) represents the best-studied example. Using a VGF deletion mutant of VACV-WR, it has been demonstrated that VGF is required for most of the ERK1/2 activation observed in VACV-infected cells (1,43).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Vaccinia virus contains two copies of the vaccinia growth factor (VGF) gene, one at each end of its genome, flanked by inverted terminal repeats (5). Previous studies showed that VGF, an epithelial growth factor-like peptide, binds to and activates erbB1 (also called the EGF receptor) (48), induces cellular proliferation of infected cells (5,6), and was required for viral replication (5,26). Variola virus produces the closely related smallpox growth factor that also binds erbB1 (24).…”
Section: Vaccinia Virus Preferentially Infects Differentiated Airway mentioning
confidence: 99%
“…Thus, we hypothesized that the increase in cell number following infection was due to VGF. We infected well-differentiated epithelia with virus that retains the coding regions for VGF (vp37-eGFP) or a mutant virus with the two VGF genes disrupted (VSC20) (5). By 96 h after infection with the VSC20 virus, epithelia appeared irregular, and proliferative changes were not apparent (Fig.…”
Section: Vaccinia Virus Preferentially Infects Differentiated Airway mentioning
confidence: 99%